การศึกษาแนวทางในการบรรเทาภาวะหมดไฟในการทำงานของตำรวจตรวจคนเข้าเมือง - ศิพงษ์ หนูเทพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This qualitative research aims to study the immigration police s job burnout, specifically job burnout level as per Maslach Burnout Inventory (MBI) and factors associated with it. An initial identification of burnout individuals revealed that 22 of 87 officers, approximately 25 percent, who responded to the MBI assessment were burned out in all three aspects: exhaustion, cynicism, and professional efficacy.A semi-structure interview with twelves officers identified as burned out suggested that burnout symptoms these officers described were consistent with Maslach’s. The descriptions matched well with the first two aspects except professional efficacy. When put their performance in context, their answers suggested that they were able to satisfy most indicators of work efficacy. Interview also found contextual factors of the burnout being low monetary incentive (i.e., low salary, having to split over time payment with the entire country immigration police who do not get as much traffic as where they work), micromanagement from their superiors, some unnecessary commands from their superiors. Research implications and suggestions for burnout.